2012
DOI: 10.1248/bpb.35.269
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Ubiquitin Ligase HRD1 Insolubilization in Amyloid .BETA. Generation

Abstract: Endoplasmic reticulum (ER)-associated degradation (ERAD) selectively retro-transports and degrades unfolded proteins accumulated in the ER. We have demonstrated that the ubiquitin ligase HRD1 involved in ERAD was significantly decreased in the cerebral cortex of Alzheimer's disease patients. Furthermore, the HRD1 level was negatively correlated with amyloid β (Aβ) production levels. Here we found that the HRD1 protein level decrease was due to its insolubilization. Moreover, these protein levels extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The results suggest that the decrease in HRD1 levels in AD is a result of its insolubilization, which may be involved in Abeta generation. 33 Insolubilization of HRD1 protein causes dysfunction of HRD1, and this dysfunction results in increased Abeta levels. It is also reported that HRD1 promotes APP ubiquitination and degradation, resulting in decreased generation of Abeta.…”
Section: Ubiquitination Enzymesmentioning
confidence: 99%
“…The results suggest that the decrease in HRD1 levels in AD is a result of its insolubilization, which may be involved in Abeta generation. 33 Insolubilization of HRD1 protein causes dysfunction of HRD1, and this dysfunction results in increased Abeta levels. It is also reported that HRD1 promotes APP ubiquitination and degradation, resulting in decreased generation of Abeta.…”
Section: Ubiquitination Enzymesmentioning
confidence: 99%
“…Beta amyloid could regulate synaptic protein degradation and function through ubiquitin pathway [136,137]. Moreover, several E3 ubiquitin ligases have been shown to promote APP degradation [138,139]. Additionally, HSA21 located genes AIRE and UBE2G2 are directly involved in the ubiquitin pathway and could contribute to the phenotype.…”
Section: Ubiquitin Proteolysismentioning
confidence: 99%
“…In addition, we found that AD-affected neurons are under ER stress and, a significant decrease in HRD1 levels in the NP-40-soluble fraction was observed in the cerebral cortex of AD patients [2], which negatively correlated with Aβ accumulation levels in the human cerebral cortex [24]. Furthermore, we found an increase in the HRD1 levels in the NP-40-insoluble fraction, suggesting protein insolubilization [25]. Because the mechanism(s) underlying the change in HRD1 solubility are unclear, we have investigated the possible roles of AD-related molecules and stresses, such as Aβ, tau, ER stress, and oxidative stress.…”
Section: Introductionmentioning
confidence: 61%